Gender identities in e-shop perfume descriptions - Nemčoková Katarína; Kráľová Zdena; Holíková Aneta; Sampey Daniel P. (Topics in Linguistics, 2021)
Perfume descriptions serve as an important persuasive tool in fragrance advertising. Scents traditionally elude clear verbal description, yet perfumes are nowadays frequently sold online, with no direct olfactory experience on the part of the consumer at the point of purchase. The products are thus often represented by metaphorical means depicting a desirable experience or portraying attractive identities of wearers, including stereotypical images of men and women. This article analyses 80 e-shop fragrance descriptions equally divided among adverts targeted at males and females. The sample texts were collected randomly from British and American e-shops, with the primary research objective to determine how male and female identities are reflected in these descriptions. The method of discourse analysis was applied and the AntConc 3.4.4 toolkit was used to calculate the frequency of words and their collocations. It was found that current female perfume descriptions on e-shops generally suppress gender stereotypes quite successfully, while gender stereotyping is more prominent in male perfume descriptions. The possible causes as well as ramifications of this disparity are also discussed.